2022
DOI: 10.4239/wjd.v13.i7.532
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and mechanism of anti-vascular endothelial growth factor drugs for diabetic macular edema patients

Abstract: BACKGROUND Diabetes is a serious public health concern in China, with 30% of patients developing retinopathy, and diabetic macular edema (DME) having the biggest impact on vision. High blood glucose level can cause retinal cell hypoxia, thus promoting vascular endothelial growth factor (VEGF) formation and increasing vascular permeability, which induces DME. Moreover, cell hypoxia can accelerate the rate of apoptosis, which leads to the aging of patients. In severe cases, optic cell apoptosis or r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Although the characteristic imaging markers of each subtype are useful for predicting patient prognosis and improving treatment strategies, our study revealed no significant differences in MRI parameters related to TP53 mutation. The TP53 gene mutation can promote the expression of vascular endothelial growth factor (VEGF), which can increase the permeability of blood vessels while inducing the growth of tumor blood vessels [ 42 ]. However, our study showed no significant association between TP53 mutation and MRI-detectable changes in angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Although the characteristic imaging markers of each subtype are useful for predicting patient prognosis and improving treatment strategies, our study revealed no significant differences in MRI parameters related to TP53 mutation. The TP53 gene mutation can promote the expression of vascular endothelial growth factor (VEGF), which can increase the permeability of blood vessels while inducing the growth of tumor blood vessels [ 42 ]. However, our study showed no significant association between TP53 mutation and MRI-detectable changes in angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Vermij et al (35) showed that the expression level of human epidermal growth factor receptor-2 (Her-2) is highly correlated with p53abn-type EC, and the overexpression of Her-2 can cause abnormality in EC cell proliferation. The TP53 gene mutation and the overexpression of Her-2 can promote the expression of vascular endothelial growth factor, which can increase the permeability of blood vessels while inducing the growth of tumour blood vessels (36), causing the release of some proteins. In addition, Meng et al (37) used APTw to identify cervical cancers of different pathological types and grades, and found that a certain amount of proteins and peptidesmay bereleased into the surrounding microenvironment during the process of tumour tissue necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-VEGF agents prevent the activation of VEGF receptors on endothelial cells and thus stop vascular endothelial hyperplasia from developing, thereby counteracting DME pathogenesis. 24 Current guidelines recommend monthly monitoring during the first 6 months of anti-VEGF treatment. 1,4 Monitoring should continue thereafter because worsening VA and CST rebound are common.…”
Section: Statement 6: Switching Therapy Is An Option For Managing Pat...mentioning
confidence: 99%